Determinación De La Flota De Acarreo Óptima A Largo Plazo, Utilizando Software Minehauld En Mina La Arena - Fabián Chávez, Janeth Mariela (2017)
The La Arena mining unit is in a process of continuous improvement in each of its operations in order to increase its profitability. Carrying is one of the most important and costly unit operations throughout the entire process, which seeks to obtain the best results and ensure production compliance, not only by working day-to-day but also by planning up to Closure of the mine, this leads to the search for alternatives that meet these requirements and allow to project based on the current data plans that lead to better results according to the conditions presented. The determination of the transport fleet was determined with historical data and mathematical calculations of a data in Excel, in a short period, referring to months and was adjusted according to the operating conditions, being an additional cost if it was necessary to incorporate a truck More, if in case the number of trucks was being overestimated, control over this was not being an unnecessary cost throughout the process. According to the studies of reserves and the life of the mine of the project "The Arena" is estimated until the year 2020, being the average production per year of 52, 000 tons of material both mineral and dismantle. In the current year a smaller tonnage was considered, the same will be worked in the same way and even to follow up to be the optimal fleet of carry and to project it in the long term. With the implementation of the software Minehauld favored to determine the fleet of optimal haul making several simulations in diverse scenarios of long term. Being a support for the short-term plans and favors the projection of a long term, monitoring and control of production compliance.